2014
DOI: 10.1016/j.canlet.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated crosstalk between chronic myelogenous leukemia cells and human bone marrow stromal cells triggers an Interleukin 8-dependent survival of leukemia cells

Abstract: a b s t r a c tChronic myelogenous leukemia (CML) is a myeloproliferative disorder characterized by the Bcr-Abl oncoprotein with constitutive tyrosine kinase activity. Exosomes are nanovesicles released by cancer cells that are involved in cell-to-cell communication thus potentially affecting cancer progression. It is well known that bone marrow stromal microenvironment contributes to disease progression through the establishment of a bi-directional crosstalk with cancer cells. Our hypothesis is that exosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 27 publications
7
134
0
1
Order By: Relevance
“…Multiple studies have focused on the role of the BM microenvironment in the pathophysiology of hematological malignancies [19,20]. However, a growing body of evidence suggests that tumors can also regulate their surrounding microenvironment, making it more amenable to their survival and development [21,22]. For instance, AML cells can induce the expression and secretion of the Axl ligand Gas6 in BM-derived stromal cells, and Gas6, in turn, can mediate the proliferation, survival and chemoresistance of Axl-expressing AML cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have focused on the role of the BM microenvironment in the pathophysiology of hematological malignancies [19,20]. However, a growing body of evidence suggests that tumors can also regulate their surrounding microenvironment, making it more amenable to their survival and development [21,22]. For instance, AML cells can induce the expression and secretion of the Axl ligand Gas6 in BM-derived stromal cells, and Gas6, in turn, can mediate the proliferation, survival and chemoresistance of Axl-expressing AML cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Asparaginase is routinely used in the treatment of childhood acute lymphoblastic leukemia (ALL) due to the fact that ALL cells often depend on exogenous asparagine, as their own capacity for its production is generally low [62]. Despite this, however, not all patients respond to this therapy, which indicates there are further sources of asparagine production and potential interference with asparaginase treatment.…”
Section: Microenvironment/leukemia Cells Crosstalk: Soluble Factors Amentioning
confidence: 99%
“…Accumulating evidence demonstrated that cancer cells release higher levels of exosomes suggesting their involvement in cancer progression and microenvironment education [7,8]. Leukemia derived exosomes can also affect bone marrow microenvironment thus enhancing leukemia cell growth [9][10][11]. We will discuss the anticancer effects of plants extracellular vesicles in a following section.…”
Section: Introductionmentioning
confidence: 99%